Saqueo y depredación de nidadas de tortugas marinas, durante las temporadas 2003 a 2012, en seis playas del Golfo de Paria, Venezuela (UNED Research Journal, 2014)
Poaching and predation of sea turtle clutches, during the 2003 and 2012 seasons, on six beaches of the Paria Gulf in Venezuela. Looting and predation of nests are among the major threats to marine turtles. Six beaches of Paria Gulf, northeastern Venezuela, have been protected and had a reduction of clutch poaching and predation on leatherback (Dermochelys coriacea), green (Chelonia mydas), and hawksbill (Eretmochelys imbricata) turtles. During ten years (2003-2012) of nesting seasons (March through October) the six beaches were observed for nesting, poaching and predation. The most frequent losses are caused by poaching, followed by the common fox (Cerdocyon thous), opossum (Didelphis marsupialis) and tamandua (Tamandua tetradactila). The most poached beach is Silvano, followed by Los Garzos (main nesting beach at the site) and Cerezo, which is more distant from the conservation team activity.
Keywords: Conservation; Dermochelys coriacea; Chelonia mydas; Eretmochelys imbricata; poaching; predation; Paria Gulf.